2013
DOI: 10.1371/journal.pone.0071312
|View full text |Cite
|
Sign up to set email alerts
|

Population Cancer Risks Associated with Coal Mining: A Systematic Review

Abstract: BackgroundCoal is produced across 25 states and provides 42% of US energy. With production expected to increase 7.6% by 2035, proximate populations remain at risk of exposure to carcinogenic coal products such as silica dust and organic compounds. It is unclear if population exposure is associated with increased risk, or even which cancers have been studied in this regard.MethodsWe performed a systematic review of English-language manuscripts published since 1980 to determine if coal mining exposure was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…This review did not include related types of coal mining outside of this region that may be relevant to community health exposures as covered in recent systematic reviews by Jenkins et al (2013) of coal mining and cancer and Mactaggart et al (2016) of mining in rural communities in high-income countries. Although perhaps limiting, we felt justified focusing on the potential health effects from MTR mining in the Appalachian Mountains.…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…This review did not include related types of coal mining outside of this region that may be relevant to community health exposures as covered in recent systematic reviews by Jenkins et al (2013) of coal mining and cancer and Mactaggart et al (2016) of mining in rural communities in high-income countries. Although perhaps limiting, we felt justified focusing on the potential health effects from MTR mining in the Appalachian Mountains.…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…11 Studies that investigated the effects of occupational exposure to coal, a substance similar to charcoal has established the dose-response relationships with lung diseases such as pneumoconiosis and COPD. [3][4][5][15][16][17][18][19][20][21] We hypothesize that prolonged exposure to charcoal dust is associated with increased risk for manifestation of poor respiratory health outcomes among the charcoal workers. This study investigated whether exposure to charcoal dust was related to respiratory symptoms and lung function in a dose-dependent manner.…”
Section: -5mentioning
confidence: 99%
“…In relation to exposure to dust containing SiO 2 , epidemiological studies have been focused mostly on the issue of the risk of malignant neoplasms of the lungs and stomach in recent years. Regarding the mortality of miners from malignant neoplasms of the lung, the results of the individual studies vary from negative associations [6,7,13,15,16], to not significantly increased risks, to a statistically significant increase of values [10,14,16,17,18,19]. In some cases, large cohorts are followed up for a period of several decades, e.g., the US study of underground coal miners [5,6], where a recent study was in compliance with the previous studies that had found higher mortality from malignant and non-malignant respiratory diseases [20].…”
Section: Introductionmentioning
confidence: 99%